DEVELOPING STUDENTS’ SPIRITUAL AND MORAL VALUES THROUGH GEOGRAPHY LESSONS - Tuleshova Kuralay*, Zhanaeva Merey (Вестник ЗКУ, 2026)
The article examines effective ways of forming students' spiritual and moralvalues in geography lessons through game-based learning technologies. The study identifies students'initial level of understanding of social and ethical norms and analyzes the effectiveness of interactiveteaching methods in developing responsibility, cooperation, tolerance, and environmental awareness.The results confirm that game technologies significantly improve students' spiritual and moraldevelopment.